Discovery solubility measurement and assessment of small molecules with drug development in mind - Barrett, Jaclyn A.; Yang, Wenzhan; Skolnik, Suzanne M.; Belliveau, Lisa M.; Patros, Kellyn M. (Drug discovery today, 2022)
•Seamless solubility understanding requires discovery-development collaboration.•Gold standard methods in drug development map solubility of drug candidates.•Drug development solubility informs developability and drug product strategies.•Evolving drug discovery solubility assays incorporate development practices.•Drug discovery solubility assays benefit discovery-development learning cycles. Solubility is a key physicochemical property for the success of any drug candidate. Although the methods used and their rationales for determining solubility are subject to project needs and stages along the drug discovery–drug development pipeline, an artificial boundary can exist at the discovery–development interface. This boundary results in less effective solubility knowledge sharing and data integration among scientists in both drug discovery and drug development. Herein, we present a refreshed perspective on solubility. Solubility experimentation is not a one-size-fits-all measurement; instead, we stress the importance of constructing a seamless solubility understanding of a molecule as it progresses from a new chemical entity into a drug product.